Analysis of the Influence of Domestic Products, Loan Interest Rates, and Residential Property Price Index on Home Ownership Credit Distribution in Indonesia for the Period 2015:TW.I – 2023:TW.III - Dondok, Clara Monica; Kumenaung, Anderson Guntur; Mandeij, Dennij (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research examines the relationship between Gross Domestic Product (GDP), interest rates and house prices on mortgages in Indonesia. Using the dynamic ECM Domowitz-Elbadawi method, this research explores the short and long term relationships between these variables. House prices are measured using the composite Residential Property Price Index in the primary market. The research results show that GDP has a positive and significant effect on mortgage distribution in the short term. On the other hand, in the long term, both interest rates and house prices have a negative and significant influence on mortgage distribution. These findings are valuable for strategic decision making in property investment and policy formulation, suggesting that increasing GDP can boost mortgage distribution, while managing interest rates and house prices is important for long-term stability.